2015
DOI: 10.1093/jme/tjv132
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Activity, Density, and Collection Efficiency of the Blacklegged Tick (Ixodes scapularis) (Acari: Ixodidae) in Mid-Western Pennsylvania

Abstract: Although Pennsylvania has recently reported the greatest number of Lyme disease cases in the United States, with the largest increase for PA occurring in its western region, the population biology of the blacklegged tick (Ixodes scapularis Say) has not been adequately characterized in western PA. We studied the seasonal activity of host-seeking I. scapularis larvae, nymphs, and adults in mid-western PA over the course of a year, including a severe winter, and determined their absolute densities and collection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 37 publications
4
21
0
Order By: Relevance
“…Seasonal distribution of tick bite-related ED encounters peaked earlier than reported LD cases with a second peak in the fall. This observation is consistent with other studies showing emergence of overwintering adult ticks and nymphs in the spring and presence of adult ticks in the fall (Falco et al, 1999;Schulze & Jordan, 1996;Simmons, Shea, Myers-Claypole, Kruise, & Hutchinson, 2015;Xu et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Seasonal distribution of tick bite-related ED encounters peaked earlier than reported LD cases with a second peak in the fall. This observation is consistent with other studies showing emergence of overwintering adult ticks and nymphs in the spring and presence of adult ticks in the fall (Falco et al, 1999;Schulze & Jordan, 1996;Simmons, Shea, Myers-Claypole, Kruise, & Hutchinson, 2015;Xu et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…Seasonal distribution of tick bite‐related ED encounters peaked earlier than reported LD cases with a second peak in the fall. This observation is consistent with other studies showing emergence of overwintering adult ticks and nymphs in the spring and presence of adult ticks in the fall (Falco et al., ; Schulze & Jordan, ; Simmons, Shea, Myers‐Claypole, Kruise, & Hutchinson, ; Xu et al., ). In contrast, both reported LD cases and LD‐related ED encounters showed a single peak in the summer thought to result from increased exposure to the nymphal stage of the tick, which emerges in the spring (Falco et al., ).…”
Section: Discussionsupporting
confidence: 92%
“…The seasonality data for the five most abundant tick species inferred by our passive surveillance data is consistent with previous records of seasonality described by other researcher [5,42,65,66], demonstrating that these types of passive data contain biologically meaningful signal.…”
Section: Discussionsupporting
confidence: 90%
“…Apart from one recent fine-scale analyses on the phenology of I. scapularis by Simmons et al [42], much of the literature on PA ticks reflects presence/absence data of I. scapularis and/or the pathogens they harbor. There have been 2 exceptions: a study of river otters that found 3 female, 1 nymphal and 1 larval I. cookei on 3 otters, and a study quantifying the ectoparasites of bats in Blair County, PA that identified 5 specimens of soft tick Ornithodoros kelleyi Cooley & Kohls [40,28].…”
Section: Discussionmentioning
confidence: 99%
“…An ideal tick surveillance programme would not only utilize multiple approaches and have a dedicated tick biologist proficient at species identification on staff, but it would also take a proactive stance that is not limited strictly to immediate threats. Since 1993 (~25 years) there have been 28 publications on ticks from Pennsylvania, and 22 of them were focused on I. scapularis and/or the microbiota (mostly on pathogens) [23, 25, 4671]. While I. scapularis is an important vector that warrants this attention, other tick species are being ignored.…”
Section: Discussionmentioning
confidence: 99%